2017
DOI: 10.1037/mot0000074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-motivational interactions: Beyond boxes-and-arrows models of the mind-brain.

Abstract: How do motivation and cognitive control interact in brain and behavior? The past decade has witnessed a steady growth in studies investigating both the behavioral and the brain basis of these interactions. In this paper, I describe such interactions in the context of the dual completion model, which proposes that motivational significance influences both perceptual and executive competition. Embracing a research agenda that attempts to understand cognition-motivation interactions highlights considerable challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…To conclude, previous work has shown that reward motivation may improve cognitive performance by boosting abstract task codes (Etzel et al, 2016) or biasing perceptual representations to prioritise sensory information relevant to current task goals (Hickey & Peelen, 2015;Pessoa, 2017;Serences, 2008;Serences & Saproo, 2010). Here we show that high reward prospect can enhance neural coding of task information as well as task-relevant sensory information, without altering representations for task-irrelevant sensory information.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…To conclude, previous work has shown that reward motivation may improve cognitive performance by boosting abstract task codes (Etzel et al, 2016) or biasing perceptual representations to prioritise sensory information relevant to current task goals (Hickey & Peelen, 2015;Pessoa, 2017;Serences, 2008;Serences & Saproo, 2010). Here we show that high reward prospect can enhance neural coding of task information as well as task-relevant sensory information, without altering representations for task-irrelevant sensory information.…”
Section: Discussionsupporting
confidence: 60%
“…Here we show that transient changes in prospective reward can also modulate task-relevant perceptual feature representations. Second, research using prospective reward cues has led to the proposal that reward motivation might benefit attentional filtering, either by enhancing task-relevant perceptual representations or supressing task-irrelevant representations (Pessoa, 2017). Hickey & Peelen (2015) found evidence for both of these mechanisms, showing that reward could either enhance or suppress perceptual representations as a function of task-relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could increase the efficiency of task reconfiguration (Braem & 720 Egner, 2018), as indexed by the improvements in behavior, while the specific rule representations 721 would remain equally structured. Nonetheless, more research is needed to properly characterize 722 the intricate interactions among proactive control and motivation (Pessoa, 2017) in rich task 723 environments, more akin to daily life situations. 724…”
Section: Flexibility 678mentioning
confidence: 99%
“…Finally, cognitive control and motivation maintain an intricate relationship during task 92 preparation (Pessoa, 2009(Pessoa, , 2017. Reward expectation boosts cue-locked activity across the FP 93 network (Parro, Dixon, & Christoff, 2017), and it has been recently linked to stronger anticipatory 94 rule encoding (Etzel, Cole, Zacks, Kay, & Braver, 2016).…”
mentioning
confidence: 99%